Monitoramento em tempo real da orientação molecular de poliestireno e em misturas com polimetilmetacrilato durante a extrusão - Santos, Adillys Marcelo da Cunha (2011)
In this work it was studied the flow orientation of pure polystyrene and its diluted mixtures with polymethylmethacrylate as second phase during extrusion process by in-line monitoring of the polarized transmitted light intensity. The optical device is attached to the extruder exit by means of a slit-die possessing bores fitted with borosilicate transparent glass windows where light may go through to reach the flow. Upon pressurization, the windows internal structure changes which influences its optical response. The expected sine-square fitting relating transmitted light intensity and applied pressure on the windows is applied to the data. Doing that the software is able to deduct the glass windows strain birefringence from the polymer flow birefringence contribution. Stopping the feed allowed the in-line monitoring at a continuous decrease in shear rate replacing the time-consuming and waste of material of the steady-state. Amidst the samples evaluated, the higher viscosity polystyrene presented a high orientation level inducing an optical path difference above the half first order (OPD > 275nm). On shear rate decreasing the orientation of the flowing polymer reduces, displayed by the optical detector as a change in the transmitted light intensity, following a sinusoidal curve. Addition of a second phase to the PS matrix both lower the transmitted light intensity due to the turbidity created by the scattering particles presented in the medium and shifts the curves maxima to higher pressure values. The latter case is explained by the generation of methyl methacrylate monomer that diffuses into the PS matrix reducing its viscosity and so the chain orientation. Statements above revealed a vector called Azimuthal influence of the Concentration.